Technology Strategies for Low-Carbon Economic Growth : A General Equilibrium Assessment - Wing, Ian Sue; Timilsina, Govinda (World Bank, Washington, DC, 2016)
This paper investigates the potential for developing countries to mitigate greenhouse gas emissions without slowing their expected economic growth. A theoretical frame- work is developed that unifies bottom-up marginal abatement cost curves and partial equilibrium techno-economic simulation modeling with computational general equilibrium (CGE) modeling. The framework is then applied to engineering assessments of energy efficiency technology deployments in Armenia and Georgia. The results facilitate incorporation of bottom-up technology detail on energy-efficiency improvements into a CGE simulation of the economy-wide economic costs and mitigation benefits of technology deployment policies. Low-carbon growth trajectories are feasible in both countries, enabling reductions of up to 4 percent of baseline emissions while generating slight increases in GDP (1 percent in Armenia and 0.2 percent in Georgia). The results demonstrate how MAC curves can paint a misleading picture of the true potential for both abatement and economic growth when technological improvements operate within a system of general equilibrium interactions, but also highlight how using their underlying data to identify technology options with high opportunity cost elasticities of productivity improvement can lead to more accurate assessments of the macroeconomic consequences of technology strategies for low-carbon growth.